Where Are All the Woke Kids? Lived Experience First: Reordering Media Literacy Practice to Examine 17–18-year-olds’ Interpretations of Gender Performativity and Media - Usmar, Richard Patrick (Auckland University of Technology, 2026)
Putting their everyday experiences first, this thesis explores how senior high school students in Aotearoa/New Zealand make sense of gendered identities through media literacy practices. It is presented in two manuscript-style chapters, each structured as a standalone article submitted for academic publication. The first paper investigates students’ ideas about gendered identities by reflecting on individuals they admire, the performativity and values of admiration in real life, and the connections they make to media representations. Drawing on Judith Butler’s theory of gender performativity, the study shows students—particularly young women—demonstrate encouraging levels of critical awareness, while many young men largely fail to show critical thinking, resist notions of gender equality and fall back on essentialist assumptions. The second paper extends this exploration by focusing on how students engage with an ambiguous media text—specifically one that invites audiences to consider multiple readings. By analysing student responses to a video clip that deliberately avoids presenting a fixed message, this study allows students to offer personal reflections and make visible their own ideas about gendered identities. This pedagogical approach empowers learners to examine how representations of gender both conform to and resist dominant norms, fostering deeper critical engagement and self-awareness. Again, responses reveal strongly gendered patterns in media literacy competencies: broadly speaking female students critically engage with context and representation, while male students often reinforce dominant tropes. Together, the papers highlight a concerning persistence of gender essentialism among older male teens, despite recounting real-life admiration for people regardless of their gender identity. The thesis argues for the importance of embedding critical, gender-conscious media literacy into classrooms—both to challenge ingrained assumptions and to support young people in understanding how identity, representation, and social discourse interact with the media they consume and their lived experiences.